Studies on body composition of judoists - Ikai, M.; Fukunaga, T.; Toheda, H. (Association for the Scientific Studies on Judo, Kodokan, 1969)
For better understanding of working capacity, it may be useful to know the relationship between the sizes of the tissue of the body (as a mass) and their function. The measurement of the subcutaneous fat by means of the skinfold caliper or x-ray photograph is often made for estimation of the body composition. However, by this method, it is not possible to measure the cross-section of the tissue. Recently, the apparatus of ultrasonic photography was exploited, which makes it possible to observe directly the cross-section of the tissue. On the other hand, a physical method which is called the "densitometory" has been used as a method to calculate the weight or ratio of the whole body compartments. The purpose of this study is to analyse the body composition of Judoists by these methods above mentioned.